2018
DOI: 10.1016/j.jneuroling.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of linguistic and verbal short-term memory components of language abilities in aphasia

Abstract: Some current models of aphasia emphasize a role of short-term memory in the processing of language and propose that the language impairment in aphasia involves impairment to cognitive processes that activate and maintain representations of words over the time-period needed to support single word and multiple word tasks, including verbal span tasks. This paper reports normative data from 39 people with aphasia and 16 age-matched neurotypical controls on a test battery for aphasia that assesses effects of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 63 publications
3
47
1
Order By: Relevance
“…In these tasks, two words or pseudowords are presented and participants provide a yes/no response to indicate whether the two items are identical. Each task is composed of 44 pairs of one-or two-syllable words/pseudowords, with nonmatching stimuli differing by a single phoneme (Martin et al, 2018). All four participants who failed to meet the minimum pure-tone hearing threshold performed significantly above chance on these functional speech perception tasks (all at p < .0001), demonstrating adequate hearing ability for the tasks utilized in this study.…”
Section: Hearing Screeningmentioning
confidence: 83%
See 1 more Smart Citation
“…In these tasks, two words or pseudowords are presented and participants provide a yes/no response to indicate whether the two items are identical. Each task is composed of 44 pairs of one-or two-syllable words/pseudowords, with nonmatching stimuli differing by a single phoneme (Martin et al, 2018). All four participants who failed to meet the minimum pure-tone hearing threshold performed significantly above chance on these functional speech perception tasks (all at p < .0001), demonstrating adequate hearing ability for the tasks utilized in this study.…”
Section: Hearing Screeningmentioning
confidence: 83%
“…This task requires a yes/no response to 20 items including questions that are biographical, environmental, and noncontextual/grammatically complex in nature. For word-level comprehension, we used the lexical comprehension task, a 48-item auditory word-to-picture matching task developed by Martin, Minkina, Kohen, and Kalinyak-Fliszar (2018), adapted originally from the Philadelphia Comprehension Battery for Aphasia (Martin et al, 2018;Saffran, Schwartz, Linebarger, Martin, & Bochetto, 1988). In this task, participants hear a word and point to the target item in a field of four semantically related pictures.…”
Section: Auditory Comprehension Tasksmentioning
confidence: 99%
“…In addition to Study 1's assessments, these participants were given the following non-linguistic cognitive assessments before treatment: the Wechsler Adult Intelligence Scale Digit Span Forward 25 and Backward to measure verbal short-term memory; the Visual Recognition subtest of the Doors and People Test 26 and the Corsi block-tapping test 27 to measure visual short-term memory; and two visuospatial tasks (i.e., Geometric Matching and Inclusion). While the Digit Span tasks required participants to repeat numbers and may have involved linguistic processing, 28 they also required participants to temporarily maintain and manipulate information and are traditionally used to assess non-linguistic cognitive skills, such as attention and short-term memory. Thus, they will be referred to as nonlinguistic cognitive tasks in this study to distinguish them from traditional language tasks (e.g., Boston Naming Test/lexical retrieval).…”
Section: Methods -Studymentioning
confidence: 99%
“…We have investigated the effects of time passage on word retrieval by adding a temporal component (response delay) to word retrieval tasks (Martin et al, 1996, 2018; Martin and Dell, 2017). These studies have revealed some intriguing findings that we investigate further in this study: some aphasic individuals perform more poorly after a time delay while others benefit from additional time to respond.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed some intriguing findings that we investigate further in this study: some aphasic individuals perform more poorly after a time delay while others benefit from additional time to respond. Here, we provide some data from the Temple Assessment of Language and Short-term memory in Aphasia (TALSA; Martin et al, 2018) that demonstrate the change in accuracy of naming following a response delay and (2) test the hypothesis that better or worse performance on delayed naming tasks maps onto deficits of transmission or maintenance, respectively. To test this claim, we created a new version of the model of word production, the Semantic-Phonological Model (SP), which has been used in many of our studies of word production, but most recently in a study of Dell et al’s (2013) that identified the neural correlates of semantic and phonological components of word processing.…”
Section: Introductionmentioning
confidence: 99%